Intervensi Penyetaraan Jabatan: Analisis Efektivitas Penyetaraan Jabatan Administrasi Ke Jabatan Fungsional Pada Sekretariat Daerah Provinsi Maluku Utara - Hadi Tuasamu; Hartaty Hadady; Johan Fahri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Simplification of the structure and equalization of administrative positions is a bureaucratic streamlining program to realize fast, effective, and efficient public services, As is the priority program of the leadership of the president and vice president. The purpose of this study analysis is to analyze the effectiveness of the policy of equalizing administrative positions to functional positions in the Regional Secretariat of North Maluku Province. This study uses a descriptive analysis approach to explain and analyze the effectiveness of equalization of positions. The study data used is in the form of literature studies. The results of the study analysis show that the policy of equalizing administrative positions to functional positions has not been implemented effectively. The impact on the equalization of administrative positions into functional positions is still in accordance with the indicators of organizational efficiency. Administrative officers who are transferred to majority functional positions do not meet the educational and competency requirements required in the functional positions they will occupy, because the equalization of positions provides a lot of tolerance for the requirements of functional positions.